ANALISIS YURIDIS PELAKSANAAN KEWENANGAN JAKSA SEBAGAI PENUNTUT UMUM DAN PENYIDIK DALAM PENANGANAN TINDAK PIDANA KORUPSI BERDASARKAN UNDANG-UNDANG NOMOR 16 TAHUN 2004 TENTANG KEJAKSAAN REPUBLIK INDONESIA - Sealtiel, Marselly; Firmansyah, Hery (Jurnal Hukum Adigama, 2020)
The handling of corruption crimes committed by the prosecutor's office as investigators and public prosecutors has caused many problems, both internally and externally, the prosecutor's office. The Attorney General's Office carries out its duties and powers based on Law Number 16 of 2004 concerning the Public Prosecution Service of the Republic of Indonesia. The problem to be discussed in this research is how the process of carrying out investigations and prosecutions in the handling of corruption crimes committed by the prosecutor's office based on laws and whether it creates a conflict of interest when it is carried out by the same prosecutor in different work functions. This study uses a normative research method which is sourced from secondary data from a literature study with a statutory approach. The results of the study indicate that in the process of implementing the authority of investigation and prosecution by the prosecutor, it still causes problems because there is no renewal or adjustment (harmonization) between regulations. In practice, the prosecutor's office in carrying out investigations and prosecutions using the one-stop system is an efficiency in the case handling process and even the ease of coordinating under one roof. Limited human resources within the prosecutor's office mean that there are personnel who carry out the work of investigating and prosecuting at the same time, even though structurally there is separation. So that in practice it creates a conflict of interest that impacts objectivity and personnel independence.